INTEGRATION OF EDUCATIONAL COMPONENTS IN THE TRAINING OF FUTURE MASTERS OF PHARMACY - Садогурська, Катерина; Грешко, Юлія; Басараба, Роксолана (SWorldJournal, 2025)
The article analyzes the integration of three key professionally oriented disciplines—Pharmaceutical Management and Marketing, Pharmaceutical Law, and Introduction to Pharmacy—in the development of core competencies among students of the master’s educati